Die Frankfurter Stättigkeit als Element zur Normierung der Bedingungen jüdischer Existenz in den Jahren 1462 bis 1614 - Burger, Thorsten (Aschkenas, 2016)
The Stättigkeit of Frankfurt as an element of standardization of the conditions of the Jewish community in the years 1462 to 1614: Frankfurt am Main had had one of the oldest, largest and most important Jewish settlements within the Holy Roman Empire. In the imperial city the term Stättigkeit was used from the Middle Ages onwards to denote the right of residence and to describe the special status of the Jews within Frankfurt society. Stättigkeit referred to political, legal, commercial and social aspects concerning Jewish residents in Frankfurt as well as to foreign Jews who stayed in the city temporarily or were passing through. The essay describes the development and content of the regulations in the Stättigkeit from 1462 - when the Jews of Frankfurt were ordered to move into the Ghetto - up until the Fettmilch uprising in 1614. The author shows that the residence code gave the Jews a high degree of freedom to act as well as a stable legal framework. However, the Stättigkeit also imposed restrictions on their daily life, for instance regarding questions of trade.